2015
DOI: 10.2967/jnumed.114.147843
|View full text |Cite
|
Sign up to set email alerts
|

68Ga-EDTA PET/CT Imaging and Plasma Clearance for Glomerular Filtration Rate Quantification: Comparison to Conventional 51Cr-EDTA

Abstract: Glomerular filtration rate (GFR) can accurately be determined using 51 Cr-ethylenediaminetetraacetic acid (EDTA) plasma clearance counting but is time-consuming and requires technical skills and equipment not always available in imaging departments. 68 Ga-EDTA can be readily available using an onsite generator, and PET/CT enables both imaging of renal function and accurate camera-based quantitation of clearance of activity from blood and its appearance in the urine. This study aimed to assess agreement betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 30 publications
4
45
0
1
Order By: Relevance
“…Thirty minutes after reincubation of LLC-PK 1 proximal tubule cells previously exposed to 11 C-metformin, 40% of the accumulated dose was lost, showing that 11 C-metformin is not trapped in the cells. This finding is consistent with previous observations from studies examining the kinetics of cold metformin, which demonstrated that more than 90% of the absorbed dose is eliminated by the kidneys (8,9). Moreover, the autoradiography studies provided evidence that there is a high cortical uptake with rapid concomitant elimination and accumulation of 11 Cmetformin in the medullary parts, supporting the view that there is a high renal extraction of 11 C-metformin.…”
Section: Biodistribution and Dosimetrysupporting
confidence: 81%
See 1 more Smart Citation
“…Thirty minutes after reincubation of LLC-PK 1 proximal tubule cells previously exposed to 11 C-metformin, 40% of the accumulated dose was lost, showing that 11 C-metformin is not trapped in the cells. This finding is consistent with previous observations from studies examining the kinetics of cold metformin, which demonstrated that more than 90% of the absorbed dose is eliminated by the kidneys (8,9). Moreover, the autoradiography studies provided evidence that there is a high cortical uptake with rapid concomitant elimination and accumulation of 11 Cmetformin in the medullary parts, supporting the view that there is a high renal extraction of 11 C-metformin.…”
Section: Biodistribution and Dosimetrysupporting
confidence: 81%
“…Recently in The Journal of Nuclear Medicine, PET/CT was used in conjunction with 68 Ga-ethylenediaminetetraacetic acid (EDTA) to measure the glomerular filtration rate (8), suggesting that PET/CT is a suitable methodology to also study the renal and hepatic handling of cationic drugs, but so far no specific cation tracer has emerged for renal PET studies. The ideal tracer has high affinity and is specific for the OCT2 transporter, has negligible metabolism and plasma protein binding with a high first-pass renal extraction, and is excreted in high concentrations in the urine.…”
mentioning
confidence: 99%
“…One of the most promising tracers is 68 Ga-EDTA, which was recently introduced for renal PET imaging (19,20). In a clinical study comprising 31 patients, Hofman et al (20) confirmed good agreement of GFR estimation with 68 Ga-EDTA PET and 51 Cr-EDTA plasma clearance. A disadvantage of 68 Ga-labeled tracers is the requirement of costly on-site generators, although the availability of 68 Ga is currently improving because of the increased use for somatostatin receptor PET imaging.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, several PET tracers have been developed as potential candidates for quantitative renal imaging including 68 Ga-and 18 F-labeled compounds (16)(17)(18). One of the most promising tracers is 68 Ga-EDTA, which was recently introduced for renal PET imaging (19,20). In a clinical study comprising 31 patients, Hofman et al (20) confirmed good agreement of GFR estimation with 68 Ga-EDTA PET and 51 Cr-EDTA plasma clearance.…”
Section: Discussionmentioning
confidence: 97%
“…However, there is a range of other agents that could rapidly enter into routine nuclear medicine practice. These include agents for renal scanning [22] and ventilationperfusion imaging [23]. Table 21.2 provides a list of Ga-68-labelled agents that are used clinically in my department.…”
Section: The Rise and Rise Of Imagingmentioning
confidence: 99%